Extraction of dl-anabasine from Alangium platanifolium root using an emulsion liquid membrane. Issue 5 (22nd January 2015) - Guo, Zhifeng; Su, Huidan; Cai, Ru; Ma, Xiaoli
Abstract : An experimental study on the extraction ofdl -anabasine from Alangium platanifolium root (APR) using an emulsion liquid membranes system (ELMs) has been reported. Abstract : An experimental study on the extraction ofdl -anabasine from Alangium platanifolium root (APR) using an emulsion liquid membranes system (ELMs) has been reported. The ELMs was assembled using a butadiene styrene rubber emulsifier to prepare the emulsion, instead of surfactant Span 80, and acetic acid and kerosene as the carrier and diluent solution, respectively. The extraction time, pH, and volume ratio of the styrene rubber emulsifier in the membrane phase were examined, and the optimum reaction condition was determined. Under such a condition, an appropriate pH gradient in the feed and in the strip aqueous phase was set up. The selective separation ofdl -anabasine from a matrix of raw APR or processed APR demonstrated that facilitated transport was achieved in the ELMs. A dynamic extraction ofdl -anabasine provided a reasonable fit for the amount extracted versus time in the ELMs, which is based on mass transfer across the aqueous boundary layer, interfacial chemical reaction, and diffusion in the emulsion globule. Comparisons of the amount ofdl -anabasine extracted from raw APR and from processed APR between the liquid–liquid extraction (LLE) and ELM extraction were performed for both qualitative and semi-quantitative analysis using GC/MS. The results showed that the relationship between the extraction amount ofdl -anabasine and the extraction time is a bell-shaped curve, as the extraction amount ofdl -anabasine reached its maximum at 2 min, and the amount then decreased with either increasing or decreasing extraction time. The amount ofdl -anabasine extracted using ELMs is three times greater than that extracted using LLE.